Monitoring Cytokine Levels in COVID-19 Overexposed and Vaccinated Volunteers - D. D. Briukhova; V. I. Dubrovina; N. O. Kiseleva; K. M. Korytov; A. B. Pyatidesyatnikova; V. A. Vishnyakov; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. COVID-19 is accompanied by high production of cytokines - immune molecules, imbalanced regulation of which leads to disruption of the immune response. Therefore, the study of cytokine status in both vaccinated and re-vaccinated patients is necessary to develop an immunoprophylaxis strategy for COVID-19. Aim. To evaluate the cytokine status in COVID-19 survivors and vaccinated employees of a health care facility against this disease. Materials and Methods. Production levels of cytokines (IL-4, IL-10, IFN-γ and TNF-α) were determined by quantitative enzyme immunoassay in serum of 144 volunteers. Results and discussion. A significant 1.5-fold increase in IL-10 and 2.0-fold increase in TNF-α was found in the group of re-invaccinated overinfected volunteers, and a 2.0-fold decrease in IL-4 compared with the vaccinated group. An inverse correlation between IL-4 and IFN-γ levels and timing after the disease was detected. A significant decrease in IL-4 in survivors (Omicron variant) and an increase in IL-10 in the survivors at the beginning of the pandemic as compared to other re-vaccinees was established. In the vaccinated group, regardless of the vaccine used, IL-10 and TNF-α decreased significantly after revaccination. No statistically significant differences were found between the cytokine status parameters in the survivors before and after vaccination. The predominance of the cellular component of immunity was established in all the examined groups, and the highest proportion of persons with a humoral immune response was detected among the vaccinated volunteers, while the highest proportion of persons with a mixed immune response was detected among the overexperienced non-vaccinated patients. Conclusions. The results obtained supplement the available data on coronavirus infection and indicate the need for further research.